CERVICITIS CHRONIC ET CAUSA TUBERCULOUS: A CASE REPORT - Siregar, Maurizka Juwita; Djais, Taufik Hidayat; Nugraheni, Enny (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Tuberculous cervicitis is a rare form of genital tuberculosis that often mimics cervical cancer due to similar symptoms, such as abnormal vaginal bleeding and vaginal discharge. Early detection is crucial to prevent misdiagnosis and mistreatment. A 37-year-old woman presented with six months of vaginal bleeding, postcoital bleeding, and recent  vaginal discharge. Physical examination revealed an irregular cervical lesion, but laboratory and imaging findings were inconclusive. A conization biopsy revealed granulomatous inflammation with caseous necrosis, confirming tuberculous cervicitis. Acid-fast bacillus staining was negative. The patient was treated with standard antituberculous regimen, resulting in symptom resolution and clinical impprovement. Tuberculous cervicitis is often missed due to its rarity and malignancy-like symptoms. Diagnosis relies on histopathology, as microbiological confirmation is difficult. Prompt antituberculous treatment prevents serious complications. Surgical intervention may be necessary for both diagnosis and treatment.  Conclusion: Tuberculous cervicitis should be considered in cases of chronic cervicitis, especially in endemic areas. Timely diagnosis and treatment promote a good prognosis and prevent unnecessary invasive procedures.